Overexpression of methyl-CpG-binding protein 2 and autoimmunity: Evidence from MECP2 duplication syndrome, lupus, MECP2 transgenic and Mecp2 deficient mice - Sawalha, Amr H. (2013)
Methyl-CpG-binding protein 2 (MeCP2) is a key transcriptional regulator that can induce either silencing or activation of target genes. Genetic polymorphisms in the MECP2/IRAK1 locus have been associated with increased susceptibility to multiple autoimmune diseases such as lupus, primary Sjogren's syndrome, and more recently rheumatoid arthritis. Data from our group suggest that the disease risk variant in this locus is associated with gain of MeCP2 function. Recent findings indicate that MECP2 duplication in human results in defective T helper cell type 1 (T(H)1) response and IFN-γ production. Herein, we discuss the data from children with MECP2 duplication, human lupus, and from the human MECP2 transgenic and Mecp2 deficient mice to support a link between MECP2 overexpression and autoimmunity. We also provide findings from an Mecp2 deficient mouse that independently support a role for MeCP2 in the immune response and specifically in IFN-γ expression.